Analisis Indikator Laporan Berkelanjutan Universitas - Dyah Erina; Sri Pujiningsih (Wahana Riset Akuntansi, 2022)
Universitas Negeri Malang (UM)'s commitment to sustainable development is contained in the campus green policy. However, UM’s have not yet presented a sustainability report that can be accessed by stakeholders. Therefore, this study aims to identify indicators of the sustainability report of UM’s based on the Global Reporting Initiative (GRI), the Campus Sustainability Assessment Instrument (IPKK) and UI green metric. This research uses a case study strategy and content analysis. The research data were obtained from the UM website, reports and documents related to the research theme. The results showed that the profile of the UM's sustainability report was 21% of the 53 aspects in the GRI indicator, 20% of the twenty aspects of the IPKK, and ranked 615 internationally and 48 nationally from the UI Green Metric.Keywords: GRI, Sustainability, higher education